Socialization of Skills Development for Special School (SLB) Students with Disabilities in Pekanbaru City - Nababan, Domia Cindirella; Asriwandari, Hesti (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Disability is a condition where a person experiences physical, mental, intellectual and sensory limitations for a long time, so that he will experience interference or obstacles in interacting and carrying out an activity with the community environment. Including having skills, of course, it is not easy for children with disabilities to be able to develop every interest or talent that has been bestowed on them. The purpose of this study is to analyze and find out how with the limitations possessed by coaching students can create or develop skills in the extraordinary school of the Pekanbaru City Coach, because children with disabilities are children with special needs different from normal children in general so it is not easy, especially for teachers to be sensitive or understand in recognizing and developing skills for them. The method used in this study is qualitative research method. The informants contained in this study were coaching students, teachers, and parents of SLB Pembina students. Data collection techniques used are in-depth interviews, observation, and documentation. Based on the results of the study, it was obtained regarding (1) The socialization process of skill development for children with disabilities at SLB N Pembina Pekanbaru, that is, there are several stages carried out by each teacher in debriefing to the development of skills of each coaching student, (2) Obstacles experienced by teachers in socializing skill development for children with disabilities at SLB N Pembina Pekanbaru, including suitability in communicating and difficulties in managing the emotions of coaching students.